Pondok Pesantren Bustanul Ulum Mlokorejo Puger Jember Dalam Pemberdayaan Karakter Santri: Bustanul Ulum Islamic Boarding School, Mlokorejo Puger Jember, in the Empowerment of Students' Character - Dewi Nurul Qomariyah (Fenomena, 2016)
Islamic boarding schools face critical challenges in balancing religious tradition with modern demands for character empowerment. A central theoretical question is how pesantren can serve not only as centers of religious transmission but also as strategic institutions for character building and social transformation. This study analyzes the forms and methods of character empowerment implemented at Pondok Pesantren Bustanul Ulum. A qualitative descriptive approach was used, drawing on interviews, observations, and documentation to collect data from caregivers, teachers, and administrators. The findings show that character empowerment is achieved through three main methods: habituating routine religious and social activities, such as congregational prayers, fasting, and social responsibility; role modeling by kyai, ustadz, and senior students; and strict enforcement of discipline based on pesantren regulations. These methods are integrated with both formal and non-formal education within the Ahlussunnah wal-Jama’ah framework. The study concludes that the pesantren successfully develops students’ religious devotion, noble character, independence, and social awareness. It is recommended that other pesantren adopt similar structured character programs and that further research explore the long-term impact of these methods on students’ lives after graduation. Keberadaan pondok pesantren menghadapi tantangan krusial dalam menyeimbangkan tradisi keagamaan dengan tuntutan modern terhadap pemberdayaan karakter. Peta masalah teoretisnya terletak pada bagaimana pesantren tidak hanya berfungsi sebagai pusat transmisi agama, tetapi juga sebagai lembaga strategis pembentukan karakter dan transformasi sosial. Penelitian ini bertujuan menganalisis bentuk dan metode pemberdayaan karakter yang diterapkan di Pondok Pesantren Bustanul Ulum. Metode yang digunakan adalah pendekatan deskriptif kualitatif melalui wawancara, observasi, dan dokumentasi terhadap pengasuh, ustadz, serta pengurus pondok. Hasil penelitian menunjukkan bahwa pemberdayaan karakter dilakukan melalui tiga metode utama: pembiasaan kegiatan rutin keagamaan dan sosial seperti shalat berjamaah, puasa sunnah, serta tanggung jawab sosial; keteladanan dari kiai, ustadz, dan santri senior; serta penegakan disiplin berdasarkan peraturan pesantren. Metode-metode ini diintegrasikan dengan pendidikan formal dan nonformal dalam kerangka Ahlussunnah wal-Jama’ah. Kesimpulannya, pesantren ini berhasil membentuk karakter santri yang beriman, berakhlak mulia, mandiri, dan peduli sosial. Rekomendasinya, pesantren lain dapat mengadopsi program serupa dan penelitian lebih lanjut perlu mengkaji dampak jangka panjang metode tersebut.